Legal Certainty Regarding The Right to Build on PT. KAI Land in the City of Medan - Muhammad Ali Adnan; Matius Lewi Sinaga; Vincent Owen Tieson; Ernita Br Ginting; Atika Sunarto (Law Development Journal, 2026)
Land control by communities over state-owned assets, particularly land managed by PT Kereta Api Indonesia (KAI), raises legal issues concerning the certainty of land rights. This phenomenon occurs when communities occupy land over a long period without a valid legal basis, giving rise to conflicts between formal legality and social reality. The problem becomes more complex when the land is granted Building Use Rights to third parties. This study employs a normative juridical method with statutory, conceptual, and empirical approaches, and is analyzed qualitatively. The results indicate that Building Use Rights over PT KAI’s land assets remain legally valid if issued in accordance with applicable regulations; however, in practice, they are often ineffective due to physical occupation by communities. Therefore, resolving such conflicts requires an integrated approach through administrative structuring, legal measures, and non-litigation mechanisms such as mediation, relocation, and compensation in order to achieve equitable legal certainty.